Neolithisation of the Karst - Fabec, Tomaž (Arheološki vestnik, 2003)
The author presents his view of the question of theneolithisation of the Karst. It derives from analysis of the socio-historical contexts in which explanations of the neolithisationof the region were created, and through critical analysis ofpublished data and use of the concept of “stratigraphiccontextuality” he tries to extract a new database, on the basisof which he also provides a new picture of the process of transitionof the early Holocene hunter-gatherer communities which weredependent on biologically domesticated sources.